Fish antifreeze proteins: Computational analysis and physicochemical characterization - Hossain, Md Musharaf (International Current Pharmaceutical Journal, 2012)
Antifreeze proteins (AFPs) protect organisms from freezing and shows great diversity in structure, and they have been found in a variety of organisms. In this study, a total of 15 antifreeze proteins of fish were selected where they represent distinct physicochemical and structural features. The present paper uses bioinformatics approach to describe the physiochemical, functional and structural properties of Antifreeze proteins. Several Physico-chemical properties such as pI, EC, AI, GRAVY and instability index are computed and provide data about these proteins and their properties. The result of primary structure analysis infers that, fish antifreeze proteins are mostly hydrophobic. Disulfide bridges and secondary structures were analyzed using CYS_REC and SOPMA respectively. The three dimensional structure of Antifreeze proteins is predicted by using three homology modeling server Geno3D, Swiss-model and CPHmodels. The model was evaluated with PROCHECK, WHAT IF, and ProSA programs. Model visualization and analysis was done with Pymol. These structures will provide a good foundation for functional analysis of experimentally derived crystal structures. Key Words: Antifreeze Proteins; Computational tools; hydrophobicity; homology modeling; isoelectric point. DOI: http://dx.doi.org/10.3329/icpj.v1i2.9412 International Current Pharmaceutical Journal 2012, 1(2): 18-26